EVALUATING THE IMPACT OF ORGANIC FARMING POLICIES ON AGRICULTURE IN NIGERIA - Nwosu, Adaobi Chinyere; Bolaji, Adebayo Olayemi; Oluwatobi , Samuel; Eze , Chukwuemeka Victor (Ayden Journal of Agriculture and Allied Studies, 2024)
This comprehensive systematic review delves into the pivotal role of policy frameworks in catalyzing the adoption and expansion of organic farming in Nigeria. Despite the burgeoning global recognition of organic agriculture's benefits for environmental sustainability and food security, Nigeria's adoption rates remain modest due to formidable obstacles such as exorbitant certification costs, restricted market access, and a pervasive lack of awareness and technical expertise among farmers. This study critically examines the efficacy of existing policies, encompassing subsidies, certification schemes, and educational initiatives, and identifies strategic avenues for enhancement. It advocates for streamlined certification processes, the development of robust local and international markets for organic products, substantial investment in education and extension services, and enhanced financial support mechanisms. By addressing these challenges and leveraging identified opportunities, Nigeria can elevate its organic farming sector, paving the way for a sustainable, resilient, and economically viable agricultural future that aligns with global best practices and supports a healthier environment and economy. This review not only underscores the current limitations but also illuminates a path forward for transforming Nigeria's agricultural landscape through comprehensive policy reform and innovation